2022
DOI: 10.1101/2022.03.29.486286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent impact of schizophrenia risk genes

Abstract: Schizophrenia is a highly heritable psychiatric disorder with a complex genetic risk architecture that reflects the additive impact of hundreds of risk variants. While many schizophrenia-associated risk variants are thought to regulate the expression of target genes in a cell-type-specific manner, the mechanisms by which the effect of these myriad variants combine to contribute to risk remain unclear. Here we apply a CRISPR-based approach to evaluate in parallel twelve schizophrenia eGenes (that encompass comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 110 publications
(206 reference statements)
0
6
0
Order By: Relevance
“…The robust overlap between non-additive genes and convergent gene targets suggest a functional redundancy of within-function eGenes, suggesting that the observed subadditive impact reflected a saturation of the downstream effects of individual eGenes converging on common gene targets. Using a pooled CRISPR screen of a partially overlapping group of 10 SCZ eGenes in iGLUTs, we similarly reported that the strength of convergence increased with gene number and that the specificity of convergence increased with the degree of functional similarity and co-expression between eGenes 47 . Convergent genes downstream of SCZ eGenes were showed cross-disorder enrichment targets for psychiatric risk genes, suggesting that they may underlie shared clinical hallmarks and pleiotropy of risk 47 .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The robust overlap between non-additive genes and convergent gene targets suggest a functional redundancy of within-function eGenes, suggesting that the observed subadditive impact reflected a saturation of the downstream effects of individual eGenes converging on common gene targets. Using a pooled CRISPR screen of a partially overlapping group of 10 SCZ eGenes in iGLUTs, we similarly reported that the strength of convergence increased with gene number and that the specificity of convergence increased with the degree of functional similarity and co-expression between eGenes 47 . Convergent genes downstream of SCZ eGenes were showed cross-disorder enrichment targets for psychiatric risk genes, suggesting that they may underlie shared clinical hallmarks and pleiotropy of risk 47 .…”
Section: Discussionmentioning
confidence: 82%
“…Using a pooled CRISPR screen of a partially overlapping group of 10 SCZ eGenes in iGLUTs, we similarly reported that the strength of convergence increased with gene number and that the specificity of convergence increased with the degree of functional similarity and co-expression between eGenes 47 . Convergent genes downstream of SCZ eGenes were showed cross-disorder enrichment targets for psychiatric risk genes, suggesting that they may underlie shared clinical hallmarks and pleiotropy of risk 47 . Moreover, recent studies of loss-of-function autism spectrum disorder genes, albeit perturbations unlikely to be inherited in combination, also reported convergence, whether evaluated in vitro in human neural progenitor cells 48 and brain organoids 49 , or in vivo in fetal mouse brains 50 and Xenopus tropicalis 51 .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our neuronal subtype-specific 3D genome maps are accessible through the PsychENCODE Knowledge Portal (https://synapse.org) and further expand the number of Hi-C datasets from human brain 8,9,11,17,47,70,71 . Cell type-specific 3D genome analyses across the major neurotransmitter classes implicated in schizophrenia could improve the accuracy of diagnosis 72 and the targets of distal risk genes may represent novel therapeutic targets 73 .…”
Section: Discussionmentioning
confidence: 99%